The conceptualization of sosial contract in the light of the «rhetoric» of rights and freedoms as values of Europe - Городницький, А. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The paper covers a range of issues related to the reception of the modern European idea of “social contract” in modern social philosophy and philosophy of law, revealing social contract as a precondition for implementing values of freedom namely through the “rhetoric” of rights.